2020
DOI: 10.20944/preprints202009.0615.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing Oil Recovery with Hydrophilic Polymer-Coated Silica Nanoparticles

Abstract: Nanoparticles have been proposed for enhanced oil recovery (EOR). The research has demonstrated marvelous effort to understand the mechanisms of nanoparticles-EOR. Nevertheless, gaps still exist in terms of understanding the improved fluids and fluid-rock interactions by nanoparticles, which are the key driving forces for oil mobilization. This paper investigates four types of polymer-coated silica nanoparticles as additives for water flooding oil recovery in water-wet reservoirs. A series of flooding experime… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In addition, the IFT reduction can be due to the surface-active polymer molecules surrounding the surface of the NPs that provide steric repulsive forces and stabilization of the NPs suspension. Comparing the results of the IFT data from previous studies at room temperature [ 15 , 17 ], for the same NPs, the greatest IFT reduction is achieved at elevated temperature. This indicates that the wetting properties and the binding energy of the NPs to the oil/water interface increase with temperature.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In addition, the IFT reduction can be due to the surface-active polymer molecules surrounding the surface of the NPs that provide steric repulsive forces and stabilization of the NPs suspension. Comparing the results of the IFT data from previous studies at room temperature [ 15 , 17 ], for the same NPs, the greatest IFT reduction is achieved at elevated temperature. This indicates that the wetting properties and the binding energy of the NPs to the oil/water interface increase with temperature.…”
Section: Resultsmentioning
confidence: 76%
“…The authors associated the EOR effect to the NPs’ ability to decrease the injection pressure; the authors argued that displacement pressure decrease is related to the formation of a wedge film between the oil and the rock surface. More recently, Bila et al [ 15 , 16 ], Bila and Torsæter [ 17 ] carried out a series of flooding experiments with polymer-coated SiO NPs in Berea sandstone core plugs. Their studies revealed an incremental recovery ranging from 2.6% to 14% of the OOIP.…”
Section: Introductionmentioning
confidence: 99%